Proposing A Predictive Model for Assessing the Influence of Employee Empowerment on Organizational Performance - Al Mansoori, Mohamed Abdulla; Ahmad, Ahmad Nur Aizat (International Journal of Sustainable Construction Engineering and Technology, 2023)
Embracing employee empowerment in the UAE Federal National Council is an absolute necessity for achieving outstanding organizational performance. By granting employees freedom to make decisions, take initiative, and contribute their unique perspectives, it can unleash untapped potential and drive the council towards unparalleled success. Hence, the use of a novel multi-linear regression model in this study is an important step forward in understanding the relationship between employee empowerment and organisational performance. Unlike prior research, which may have ignored essential components, this model incorporates the independent variables meaningfulness, self-determination, impact, and competence. It examines how employee empowerment affects overall organisational performance by taking these essential factors into account. This novel methodology paves the way for new insights and potential breakthroughs in optimising workforce potential and attaining outstanding organisational success. The study used 115 respondents from the employees of UAE Federal National Council Organization to develop the model using multi-linear regression approach. The establish model can be used to predict the performance of UAE Federal National Council Organization by inserting the parameters of the Employee Empowerment which are Meaning; Competence; Impact; and Self-determination. Hopefully, the outcomes of this research contribute to the community of UAE Federal National Council Organization.